The Contribution of Inclusive Theology to Religious Pluralism Among Indonesian Christians - Pranoto, Fatony (Theological Journal Kerugma, 2024)
This study explores the contribution of inclusive theology in enhancing the understanding of religious pluralism among Indonesian Christians. The background of this research is the complexity of religious diversity in Indonesia and the importance of fostering interfaith harmony. This study aims to: (1) understand the experiences and perceptions of Christians regarding religious pluralism, (2) analyze the contribution of inclusive theology in enhancing the understanding of religious pluralism among Indonesian Christians, and (3) formulate the practical implications of inclusive theology in strengthening religious pluralism within the Christian community in Indonesia. Using a literature study method with a qualitative approach, this research examines the role of inclusive theology in fostering comprehension and acceptance of religious pluralism. The findings indicate that inclusive theology plays a crucial role in constructing a more open theological framework, cultivating values of tolerance, and strengthening the church’s role in fostering interfaith relationships. The practical implications of this study include the integration of inclusive theological education, interfaith dialogue, and social justice advocacy. By understanding and applying the principles of inclusive theology, Christian communities can contribute to building a more harmonious and tolerant society.